A drug utilization study to evaluate the prescribing pattern of clotrimazole dusting powder in dermatophytosis - Jakhar, Deepak; Mishra, Pallavi; Dhoot, Dhiraj; Patil, Saiprasad (International Journal of Research in Dermatology, 2026)
The drug utilization studies are essential tools for the monitoring various healthcare system. According to the world health organization (WHO), a drug utilization study is "the marketing, distribution, prescription, and drug usage in a society, leading to medical, social, and economic consequences".